2018
DOI: 10.1161/circoutcomes.117.003939
|View full text |Cite
|
Sign up to set email alerts
|

Prior Authorization Requirements for Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors Across US Private and Public Payers

Abstract: BACKGROUND:Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9is) are an innovative treatment option for patients with familial hypercholesterolemia or clinical atherosclerotic cardiovascular disease who require further lowering of low-density lipoprotein cholesterol. However, the high costs of these agents have spurred payers to implement utilization management policies to ensure appropriate use. We examined prior authorization (PA) requirements for PCSK9is across private and public US payers. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…First is that identifying candidate groups of patients through PGx panel testing and initiating PGx-guided medication in the first place can result in better outcomes and reduced overall costs. 22,34 FOURIER trial estimated that PGxguided strategy would become cost-effective if the price of PCSK9 inhibitors were to be reduced by 69% (to $4536/ year). 26 Our results upheld that finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First is that identifying candidate groups of patients through PGx panel testing and initiating PGx-guided medication in the first place can result in better outcomes and reduced overall costs. 22,34 FOURIER trial estimated that PGxguided strategy would become cost-effective if the price of PCSK9 inhibitors were to be reduced by 69% (to $4536/ year). 26 Our results upheld that finding.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, for many insurers, PCSK9 prescription needs a 3-month statin trial proven to be ineffective and also requires prior authorization. 22 PGx testing can flag patients unlikely to benefit from statins, and initiation of PCSK9 therapy instead of statin for them would be a cost-saving and efficient strategy that can avoid statin-related adverse events and circumvent the prior authorization process. Evidence on the costeffectiveness of implementing PGx panel testing, either preemptively or reactively, compared with usual care for any of the gene-drug combinations is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…If, however, the requirements for access to such new treatments are restrictive, then such a promising scenario is unlikely. 37 Indeed, some have suggested that despite their established clinical value, perceived costs and budgetary concerns relating to the use of PCSK9 inhibitors in the target patient groups have led to lower than expected uptake of these treatments. 38 This is a simplistic approach, however, which does not integrate possible rebates and discounts that may be offered by the manufacturers (It is noteworthy that, in the US, both manufacturers of PCSK9 inhibitors have lowered their price recently by 60%); indeed, recent developments suggest that the budget impact of such treatments is lower than anticipated, 39 especially when weighed against the burden of cardiovascular complications.…”
Section: Recommended Criteriamentioning
confidence: 99%
“…Furthermore, only half of PCSK9 inhibitor prescriptions received payer approval, and up to a one-third of approved prescriptions were never filled. The reasons for these low rates are due in part to insurance barriers, 3 which lead to high rates of payer rejections and increased out-of-pocket expenses for patients. 4 To date, there is limited information on patients' experiences when trying to obtain, fill, and use PCSK9 inhibitor therapy in community practice.…”
Section: Introductionmentioning
confidence: 99%